(untitled) (CIPEEX, 2024)
FEMINIZING ADRENAL TUMORS (FATS) ARE DEFINED AS EXTREMELY RARE NEOPLASMS, WITH MOST PRESENTING MALIGNANTLY. SOME OF THESE TUMORS ARE CAPABLE OF HORMONE SECRETION, WITH ESTROGEN BEING THE PRIMARY HORMONE RESPONSIBLE FOR CLINICAL SYMPTOMS. THESE TUMORS PREDOMINANTLY AFFECT MEN, REPRESENTING APPROXIMATELY 1% OF ALL ADRENAL TUMORS. MANY MEN EXPERIENCE PSYCHOLOGICAL DISTRESS DUE TO THE POOR PROGNOSIS OF FAT TREATMENT, EVEN WITH CURRENT PERSPECTIVES AND THE USE OF NEW TECHNIQUES AND MEDICATIONS. THIS STUDY AIMS TO IDENTIFY AND ASSESS THE NEGATIVE IMPLICATIONS OF FAT IN MEN. IDENTIFY AND ASSESS THE NEGATIVE IMPLICATIONS OF FAT IN MEN. THIS IS AN INTEGRATIVE LITERATURE REVIEW. DATA WERE COLLECTED FROM ELECTRONIC DATABASES, INCLUDING THE LATIN AMERICAN AND CARIBBEAN LITERATURE (LILACS) AND PUBMED CENTRAL (PMC), USING THE DESCRIPTORS: "ADRENAL REST TUMOR," "ADRENOCORTICAL CARCINOMA," AND "ADRENAL GLAND NEOPLASMS." A TOTAL OF 205 ARTICLES PUBLISHED BETWEEN 2017 AND 2023 WERE IDENTIFIED. INCLUSION CRITERIA ENCOMPASSED BOTH FREE AND PAID ARTICLES IN ENGLISH OR PORTUGUESE THAT COMPREHENSIVELY ADDRESSED THE TOPIC, RESULTING IN 10 SELECTED ARTICLES. THE ANALYSIS OF THE SELECTED ARTICLES REVEALED THAT ADRENOCORTICAL CARCINOMAS HAVE NEGATIVE PSYCHOLOGICAL, PHYSIOLOGICAL, AND PHYSICAL EFFECTS ON MEN. DESPITE THEIR RARITY, THESE TUMORS CAN MANIFEST BEFORE THE AGE OF 8 IN CHILDREN, DISPLAYING SIGNS OF PSEUDOPUBERTY IN BOYS AND ISOSEXUAL DEVELOPMENT IN GIRLS. COMMON CLINICAL MANIFESTATIONS IN MALES INCLUDE BILATERAL GYNECOMASTIA, HYPOGONADISM, FATIGUE, DECREASED LIBIDO, AND ERECTILE DYSFUNCTION DUE TO LOW ANDROGEN PRODUCTION. FURTHERMORE, THE MORTALITY RATE IN MEN WITH ADRENOCORTICAL CARCINOMA IS HIGH, WITH A 3-YEAR SURVIVAL RATE AFTER TUMOR RESECTION OF ONLY 20%. EFFECTIVE TREATMENT OF THIS MALIGNANCY IS BASED ON COMPLETE SURGICAL TUMOR RESECTION WHENEVER POSSIBLE, WITH METASTASES BEING TREATABLE THROUGH PROCEDURES INVOLVING RADIOTHERAPY AND CHEMOTHERAPY, WHERE MITOTANE IS THE ONLY APPROVED MEDICATION TO MANAGE THIS CONDITION. IN CONCLUSION, ADRENAL CARCINOMA CARRIES A POOR PROGNOSIS, NEGATIVELY IMPACTING THE LIVES OF AFFECTED INDIVIDUALS, EVEN WITH TREATMENT. DESPITE THE REPORTED LOW INCIDENCE OF THIS NEOPLASM IN THE POPULATION, FURTHER RESEARCH IS WARRANTED TO IMPROVE THE LIFE EXPECTANCY OF INDIVIDUALS WITH THIS CONDITION. ADDITIONALLY, THERE IS A NEED TO ESTABLISH EFFECTIVE CLINICAL CRITERIA TO DIFFERENTIATE BETWEEN MALIGNANCY AND BENIGNITY IN THIS TUMOR. &NBSP;